Marketing and fish processing strategies of sari ulam micro, small, and medium enterprise (MSME) in Tegal City - Salma Faridhatul Asma Nadia Azzahra; Sri Mulyani; Heru Kurniawan Alamsyah (Universitas Teuku Umar, 2025)
This study aims to analyze the strengths, weaknesses, opportunities, and threats (SWOT) factors, formulate business development strategies, and determine strategic priorities for the Sari Ulam MSME in Tegal City, a producer of local fish-based products. The research employs a descriptive quantitative method utilizing SWOT analysis and the Quantitative Strategic Planning Matrix (QSPM). Data were collected through observation, interviews, and documentation to construct IFAS, EFAS, TOWS, and QSPM matrices. The analysis reveals that Sari Ulam MSME faces constraints in production capacity, suboptimal digital promotion, and conventional human resource and financial management. Conversely, significant opportunities arise from increasing public interest in healthy food, enhanced access to digital markets, and government support. The IFAS score of 2.55 indicates a relatively balanced internal condition, while the EFAS score of 2.60 suggests that external factors are more influential. The priority strategy derived from the QSPM analysis emphasizes maintaining internal strengths while optimizing performance to enhance competitiveness and promote sustainable business development. Although limited to a single case study, these findings serve as a strategic reference for similar MSMEs. Furthermore, this study contributes to the strategic modeling of fish-processing MSMEs in coastal areas while supporting food security and regional economic growth